2021
DOI: 10.1021/acssensors.0c02676
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Distance-Based Cardiac Troponin Quantification Using Paper Analytical Devices for the Screening and the Follow-Up of Acute Myocardial Infarction, Using a Single Drop of Human Whole Blood

Abstract: This work introduces the procedure of using nonimmunoassay distance-based paper analytical devices (dPADs) to accurately measure any traces of the cardiac troponin I (TnI) in whole blood samples without the use of any external blood separation. This enables a rapid clinical diagnosis and the subsequent follow-up in regard to identifying acute myocardial infarction. These dPADs are designed and constructed to accommodate three parts: (1) a blood separation zone that is immobilized with a hemostatic agent, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Nevertheless, it could not interfere with the Aβ detection using this assay due to its small molecule, thus affecting its low positive charge and hydrophobic capacity. 32 Furthermore, we detected the signals of mixtures of Aβ protein and the interferents at the above-concentration, as indicated in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, it could not interfere with the Aβ detection using this assay due to its small molecule, thus affecting its low positive charge and hydrophobic capacity. 32 Furthermore, we detected the signals of mixtures of Aβ protein and the interferents at the above-concentration, as indicated in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 95%
“…Our results indicated that the color change from yellow to blue along the distance length of the paper was directly proportional to the TnI level, with both high sensitivity and selectivity, with a detection limit equal of 0.025 ng mL −1 . 32 According to this, it can be noticed that there were no interferences in the analysis, because TnI has a pI of 9.86, which is higher than that of most of the general proteins. Also, the high dissociation constant (p K a ) is 8.6 in the buffer solution at pH 8.0.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…3 d). In 2021, a non-immunoassay dPAD was introduced for the detection of cardiac troponin I (TnI) [ 142 ]. Without any external blood separation, TnI in whole blood samples was determined by using the dPAD with the LOD of 0.025 ng/mL.…”
Section: Optical Detection Methodsmentioning
confidence: 99%
“…Eliminating the void volume associated with a standard PSM layer for separation allowed lower volumes of blood to perform the same colorimetric assay. Similarly, a distance-based µPAD featured the same Whatman 1 filter paper with a wax patterned sample addition zone and lateral channel (40 mm x 2 mm) to yield a dried plasma output [127]. In this device, plasma separation was achieved by a hemostatic agent (3% w/v CaCO3/chitosan in 1 M acetic acid) stored in the sample addition zone, which induced clotting and blood aggregation by accelerating thrombin formation.…”
Section: Alternative Methods For Passive Separation Of Plasma Without...mentioning
confidence: 99%